(untitled) (The Macau Ricci Institute Journal, 2022)
Crises bear a great potential for risks and opportunities. The ongoing pandemic and the eruption of wars indicate first of all the risk that all that we cherish may perish and swiftly disappear in a few moments. On the other hand, crises afford us a great chance to wake up and embark on a spiritual journey. During the so-called Ignatian Year which stretched from May 2021 through July 2022 Jesuits and their partners in mission tried to explore how the gun loving Basque gentleman named Inigo got transformed into a Saint whose name referred to an early Christian martyr—“Ignatius”–who, according to his own testimony, longed to be devoured by wild beasts in his burning desire to become united with the Crucified Jesus Christ. How is it possible that a narcissistic ego may gradually be turned into an oblation poured out for the salvation of the world?